2009
DOI: 10.1111/j.1600-051x.2009.01373.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of teeth with a poor prognosis following non‐surgical periodontal treatment

Abstract: Teeth with a poor prognosis did not affect the proximal periodontium of the adjacent teeth, and progression of periodontal disease in these teeth and adjacent teeth can be prevented by non-surgical periodontal treatment in non-smokers. The risk factors for loss of teeth with a poor prognosis were the initial deepest PPD, tooth mobility and multi-rooted tooth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
7
2
3
Order By: Relevance
“…Molars affected by periodontal disease consequently developing furcation involvement usually respond less favourably to treatment compared with single-rooted teeth or molar teeth without furcation involvement (Nordland et al 1987, Loos et al 1989, Wang et al 1994. Such furcation-involved molars are at greater risk of loss following non-surgical periodontal therapy (Ekuni et al 2009), an outcome possibly related to anatomical features, such as root concavities (Al-Shammari et al 2001), cervical enamel projections , Hou et al 1994) and limited furcation entrance widths for access (Bower 1979). These can certainly impact upon the treatment of furcation-involved molars in Asian populations (Hou & Tsai 1987, 1997a.…”
mentioning
confidence: 99%
“…Molars affected by periodontal disease consequently developing furcation involvement usually respond less favourably to treatment compared with single-rooted teeth or molar teeth without furcation involvement (Nordland et al 1987, Loos et al 1989, Wang et al 1994. Such furcation-involved molars are at greater risk of loss following non-surgical periodontal therapy (Ekuni et al 2009), an outcome possibly related to anatomical features, such as root concavities (Al-Shammari et al 2001), cervical enamel projections , Hou et al 1994) and limited furcation entrance widths for access (Bower 1979). These can certainly impact upon the treatment of furcation-involved molars in Asian populations (Hou & Tsai 1987, 1997a.…”
mentioning
confidence: 99%
“…A total of 621 articles were retrieved initially by literature searches. The assessment of titles, abstracts, and full texts led to the inclusion of 24 articles in this systematic review ((Tonetti et al 1998, Checchi et al 2002, , Far-dal et al 2004, Chambrone & Chambrone 2006, Miyamoto et al 2006, Carnevale et al 2007, Faggion et al 2007, Fardal & Linden 2008, Matuliene et al 2008, Pretzl et al 2008, Ekuni et al 2009, Tsami et al 2009, Leininger et al 2010, Lorentz et al 2010, Martin et al 2010, Matuliene et al 2010, B€ aumer et al 2011, Martin et al 2011, Ng et al 2011, Costa et al 2012, Ravald & Johansson 2012, Costa et al 2013, Lv et al 2013, Costa et al 2014). The complete literature search process is reported in Figure 1.…”
Section: Articles Included In the Analysismentioning
confidence: 99%
“…The study also indicated that the prevalence of RA was higher in AgP patients (14.3%) than in those with chronic periodontitisan unfavorable crown-root ratio and root formation are related to poorer prognosis of periodontitis patients. Another study (16) suggested that a poor crown-root ratio (<1) is not related to tooth loss (TL). Further investigation is needed to determine whether a well-defined RA is a local risk factor for AgP progression.…”
Section: Introductionmentioning
confidence: 99%